EFFECT OF ACTINOMYCETES ON GROWTH OF OCIMUM SANCTUM - KUMARI, CHAMPA; A., UMADEVI; KUMAR, P. AJITH (International Journal of Current Pharmaceutical Research, 2019)
Objective: The study was aimed to isolate and identify Actinomycetes from rhizosphere soil of Malik deenar college of pharmacy, Kasaragod, Kerala, and to screen the plant growth promoting the activity of isolated actinomycetes on Ocimum sanctum. Methods: The Actinomycetes were isolated from rhizosphere region soil by serial dilution and pour plating method. Then they were identified to a generic level based on morphological characters, and biochemical characters. Plant growth promoting activity was screened by placing 3 sets of Ocimum sanctum seedlings in different pots and the shoot length was measured after 10 d and compared with control. Results: 19 different types of isolates were chosen based on their morphological characteristics and used for assessments of plant growth promoting activity. Among the 19 isolates, 17 isolates were identified as Streptomyces spp. And 2 were belongs to Nocardia spp. The actinomycetes isolates which belong to Streptomyces spp were shown plant growth promoting activity. Conclusion: The result of this study revealed that the rhizosphere soil has different types of actinomycetes, among these Streptomyces spp. are more abundant and common. These Streptomyces spp. have predominant activity on plant growth promotion with respect to Ocimum sanctum.